PERLINDUNGAN HUKUM TERHADAP KONSUMEN DALAM JUAL BELI OBAT HARUS DENGAN RESEP DOKTER MELALUI E-COMMERCE - Tan, Sri Christianty; Ibrahim, Ukas (SCIENTIA JOURNAL, 2021)
Consumer comes from the word consumer (English-American), or consument (Dutch). The meaning of a consumer or consumer depends on the position in which it is located. Literally the meaning of the word consumer is the opposite of the producer, where all the people who use the goods. Over time, aspects of human life have developed due to increasingly rapid technology. The internet is a technology that is familiar to people's lives. The advantages and ease of buying and selling have led to many consumers buying and selling activities online. One of the many items that are bought and sold online is medicine. Many medicine that should require a doctor's prescription before being bought and sold, are now sold freely in the market. In the written medicine packaging must be prescribed by a doctor but consumers can freely buy it online without a doctor's prescription. Therefore the need for consumer protection law.